Reproductive morphology of the golden tree snake Chrysopelea ornata (Serpentes: Colubridae) from Ao Nang, Krabi Province, Thailand - Thanaphon Likhityungyuen; Rujikorn Pimsorn; Tanatpon Prompa; Mongkol Pongsuchart; Panas Tumkiratiwong (Penerbit Universiti Kebangsaan Malaysia, 2022)
We monitored the reproductive morphology of the female and male Golden tree snake, Chrysopelea ornata. The females and males were collected during a year from Ao Nang, Muang Krabi, Krabi province, a southern part of Thailand. We investigated the female and male reproductive systems via anatomical and histological approaches. The results demonstrated that the reproductive tracts of females and males were located above the kidney and its right tract was more anteriorly than the left tract. Ovarian follicles were classified into the previtellogenic, early vitellogenic, and late vitellogenic follicles. Previtellogenic follicles were contained three types of cells in the multi-layered granulosa layer: small, intermediate, and large pyriform cells. This such layer becomes the single layer in which the pyriform cells were disappeared in the vitellogenic follicles. Various stages including corpora lutea, gestation, oviposition, and birth were all observed in this study. The oviductal structure of the Golden tree snake was divided into four regions: anterior and posterior infundibulum, uterus, and vagina. The anterior oviductal wall was covered by ciliated and non-ciliated cuboidal epithelial cells and a thin muscularis layer while its posterior portion was contained by ciliated and non-ciliated cuboidal and columnar epithelial cell, and a thick muscularis layer. We found the tubular ciliated glands in the posterior infundibulum. Additionally, the hypertrophied uterine glands in the uterus were observed during the vitellogenic stage. The seminiferous tubules were active simultaneously with the hypertrophied sexual segment of the kidney.